The Military Thinking and His Islamic balance in The Caliph Ali Bin Abi Talib ( peace is on him ) Compact to Malek Al Ashtar (God be pleased on him ): The Military Thinking and His Islamic balance in The Caliph Ali Bin Abi Talib ( peace is on him ) Compact to Malek Al Ashtar (God be pleased on him ) (Journal of the College of Education for Women, 2019)
AbstractThis study turns about The Military Thinking and His Islamic balance inThe Caliph Ali Bin Abi Talib ( peace is on him ) Compact to Malek Al Ashtar(God be pleased on him )The military field is very wide in all intellectual andpractically effects at The Caliph Ali Bin Abi Taleb(peace is on him ). Itsconsidered the first seed for islam ,therefore,there are a lot from militarysitutions which proved his practical experience in these affairs , and awayfrom the details of war and practical battles lets search the sample and theacademic study for fair military thinking (justice) in The Compact of Caliph Alito Malek Al Ashtar when he became the ruler of egypt.The military fair thinking determines from commander how heplanned,and how he faced the practical applications for illustrated plansCaliph Ali Bin Abi Taleb sent acompact to Malek Al Ashtar ,in military affairshe proved for him the leadership on armed forces,in addition to another dutieslike peace operations and another peace aspects ,its full of islamic fair .TheCompact was included the fair features which should be in the leader andmilitary ruler, the military thinking was intersting for the families of martyers.